2017
DOI: 10.15275/rusomj.2017.0106
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic therapy is an effective strategy for remediating neuroendocrine pathology

Abstract: Abstract:Aspects of reactivation and remediation of impaired functions of the brain and of the inner organs regulatory systems are crucial to medical science. The study presents the technique of transcranial magnetic therapy (TMT) with extremely low frequency alternating magnetic field employed for balanced activation of central nervous system function. This study was aimed to assess the effectiveness of TMT in diseases caused by hypothalamic-pituitary dysfunction. Material and Methods -90 children aged 10-16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A population-based, longitudinal study showed inverse associations between androgens and depressive symptoms, although the associations were not independent of relevant confounders (Kische et al, 2017). In another longitudinal study on children, the rTMS was effective in remediating testosterone to levels seen in age-matched controls (Bolotova et al, 2017). Besides, gonadal steroids are involved in regulating cortical excitability induced by rTMS (Bonifazi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A population-based, longitudinal study showed inverse associations between androgens and depressive symptoms, although the associations were not independent of relevant confounders (Kische et al, 2017). In another longitudinal study on children, the rTMS was effective in remediating testosterone to levels seen in age-matched controls (Bolotova et al, 2017). Besides, gonadal steroids are involved in regulating cortical excitability induced by rTMS (Bonifazi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%